Bioactive Titanium Surfaces: Interactions of Eukaryotic and Prokaryotic Cells of Nano Devices Applied to Dental Practice - Marco Cicciù; Luca Fiorillo; Alan Scott Herford; Salvatore Crimi; Alberto Bianchi; Cesare D’Amico; Luigi Laino; Gabriele Cervino (Biomedicines, 2019)
Background: In recent years, many advances have been made in the fields of bioengineering and biotechnology. Many methods have been proposed for the in vitro study of anatomical structures and alloplastic structures. Many steps forward have been made in the field of prosthetics and grafts and one of the most debated problems lies in the biomimetics and biocompatibility of the materials used. The contact surfaces between alloplastic material and fabric are under study, and this has meant that the surfaces were significantly improved. To ensure a good contact surface with the cells of our body and be able to respond to an attack by a biofilm or prevent the formation, this is the true gold standard. In the dental field, the study of the surfaces of contact with the bone tissue of the implants is the most debated, starting from the first concepts of osteointegration. Method: The study searched MEDLINE databases from January 2008 to November 2018. We considered all the studies that talk about nanosurface and the biological response of the latter, considering only avant-garde works in this field. Results: The ultimate aim of this study is to point out all the progress made in the field of bioengineering and biotechnologies about nanosurface. Surface studies allow you to have alloplastic materials that integrate better with our body and allow more predictable rehabilitations. Particularly in the field of dental implantology the study of surfaces has allowed us to make huge steps forward in times of rehabilitation. Overcoming this obstacle linked to the time of osseointegration, however, today the real problem seems to be linked to the “pathologies of these surfaces„, or the possible infiltration, and formation of a biofilm, difficult to eliminate, being the implant surface, inert. Conclusions: The results of the present investigation demonstrated how nanotechnologies contribute substantially to the development of new materials in the biomedical field, being able to perform a large number of tests on the surface to advance research. Thanks to 3D technology and to the reconstructions of both the anatomical structures and eventually the alloplastic structures used in rehabilitation it is possible to consider all the mechanical characteristics too. Recent published papers highlighted how the close interaction between cells and the biomaterial applied to the human body is the main objective in the final integration of the device placed to manage pathologies or for rehabilitation after a surgical tumor is removed.